Effects of composition, age and sterilization techniques of mother culture on the growth and yield of Volvariella volvacea (Bull.) Singer (Bangladesh Journal of Botany, 2020)
The research work was carried out to investigate the efficacy of different mother culture media viz., rice straw (T-1), rice straw and rice bran (T-2), rice husk (T-3), rice grain (T-4), maize grain (T-5), and rice straw and wheat bran (T-6) and the impact of age of mother culture and substrate sterilization techniques viz., sun dried for 8 hrs covering with transparent polythene (A-1), black polythene (A-2), blue polythene (A-3) sheet, autoclave for two hrs at 121°C (A-4), and hot water for one hr (A-5) for the commercial cultivation of Volvariella volvacea (Bull.) Singer. The maximum mycelium run rate and minimum days required for completing the mother culture were recorded in T-4. The lowest days required for primordial initiation (DRFPI) was 6 in T-1 and T-2, whereas highest DRFPI was recorded in T-3. The maximum (13.33) days required for first harvest (DRFFH) and lowest (109) number of effective fruiting bodies (NEFB) were recorded in T-3. The minimum (10.67 days) DRFFH was found in T-2 and maximum (239.30) NEFB was recorded in T-1. The lowest length and diameter (LFB and DFB) were recorded in T-5 (3.03 cm) and T-1 (1.66 cm), while highest LFB and DFB were observed in T-3 (3.20 and 2.39 cm). Maximum biological yield and efficiency were observed in rice straw and wheat bran materials. The highest NEFB, DFB, biological yield and efficiency were recorded in 30 days old of mother culture. The results revealed that combined rice straw and wheat bran were the excellent mother culture medium and 30 days old was the best age for the commercial production of paddy straw mushroom. Considering the experimental results on the sterilization techniques it may be suggested that hot water sterilization of rice straw substrate was the best sterilization technique for the commercial production and yield improvement of V. volvacea.